Property Position and Islamic Economic Law - Hardiati, Neni; F, Fitriani (Media Hukum Indonesia (MHI), 2024)
Property in Islam has a position as a pillar of life that supports the running of all activities, history records that the beginning of the Islamic struggle carried out by the Prophet SAW could not be separated from the role of his wife as a conglomerate who had advantages in financial terms. The position of this treasure is very important especially in economic activities, business, and worship, so that attention to this treasure has been prioritized by umara and scholars since time immemorial. Islam always teaches mankind to be grateful for the treasures that in their possession are used for devotion to Allah SWT and used solely to get closer to Him. In addition, it is also used for the benefit of many people in terms of helping others, for that it should be considered how to get it, its management and how to use it. The Qur'an pays great attention to the issue of wealth by giving detailed and extensive limits on property. Many scholars have opinions to know the position of this treasure including Imam Hanafi, Imam Shafi'i, Imam Maliki and others. Among their opinions is how the Shari'a establishes ways to obtain property, distribute it, develop it and so on. This was conveyed by them to be a reference and guideline so that the process of managing assets in human life does not cause damage and loss either to nature, the environment or to individuals and society.